Multisectoral Collaborative Extension Education on Social Reintegration of Children in Conflict with the Law - Wahyuni, Surita Triya; Kartika, Tuti; Aribowo, Aribowo (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2025)
The social reintegration of children in conflict with the law (CICL) is the process of returning children to their families and communities after undergoing rehabilitation. However, in practice, CICL often face negative stigma, rejection, and discrimination from their surrounding environment. Legal education efforts aimed at addressing this issue have not been optimal. In response, the researcher, together with the local community, developed a Collaborative Counseling Model on the Social Reintegration of CICL. The research process involved several stages: the development of an initial model, needs identification, model design, implementation, reflection, and the formulation of a final model. The study was conducted in Ciandam Village, Cianjur Regency. It employed a qualitative approach using the Participatory Action Research (PAR) method and involved 12 purposively selected participants. Data were collected through in-depth interviews, focus group discussions, observation, and documentation. Data analysis followed the Miles and Huberman model, supported by the qualitative data analysis software Nvivo 15. The counseling model involved multisector collaboration, including the Social Affairs Office, Education Office, Manpower Office, and the Correctional Center. A Community Working Team (Tim Kerja Masyarakat/TKM) was formed to implement the model, targeting community leaders and families of CICL as participants in the counseling activities. Prior to implementation, the model was refined in collaboration with TKM by adding target area mapping, home visits, and reassessments of CICL and their families. Following the counseling sessions, community leaders took initiative to disseminate information through tarawih keliling in Ciandam. As an outcome of this initiative, it is recommended that Societa Indonesia establish a discussion forum for parents of reintegrated CICL. The results of the study indicate that the implementation of this model was perceived as effective, efficient, and replicable in other regions. The goal of social reintegration was achieved through increased public knowledge, as evidenced by pretest and posttest assessments. The study’s key finding is an innovative collaborative network built through the exchange of ideas, suggestions, feedback, and improvements from each sector, leading to the development of a well-structured final model. The study recommends that rehabilitation institutions provide a discussion platform for parents of reintegrated CICL and conduct further research on the finalized model.